-1(x+2)-2x=-2(x+q)

Simple and best practice solution for -1(x+2)-2x=-2(x+q) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1(x+2)-2x=-2(x+q) equation:


Simplifying
-1(x + 2) + -2x = -2(x + q)

Reorder the terms:
-1(2 + x) + -2x = -2(x + q)
(2 * -1 + x * -1) + -2x = -2(x + q)
(-2 + -1x) + -2x = -2(x + q)

Combine like terms: -1x + -2x = -3x
-2 + -3x = -2(x + q)

Reorder the terms:
-2 + -3x = -2(q + x)
-2 + -3x = (q * -2 + x * -2)
-2 + -3x = (-2q + -2x)

Solving
-2 + -3x = -2q + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-2 + -3x + 2x = -2q + -2x + 2x

Combine like terms: -3x + 2x = -1x
-2 + -1x = -2q + -2x + 2x

Combine like terms: -2x + 2x = 0
-2 + -1x = -2q + 0
-2 + -1x = -2q

Add '2' to each side of the equation.
-2 + 2 + -1x = 2 + -2q

Combine like terms: -2 + 2 = 0
0 + -1x = 2 + -2q
-1x = 2 + -2q

Divide each side by '-1'.
x = -2 + 2q

Simplifying
x = -2 + 2q

See similar equations:

| 4x-2(x+7)=-45 | | -5x-125=44+8x | | 17=-5(3x-7)+6(-8+5x) | | -8.5h-7.5-9.5=-15.5 | | 2x+5y-9=0 | | 6x-9=3x+11 | | y-6=-2(x+2) | | (X-10)-4=12 | | 1.1y-(y-0.6)+0.3=0 | | 3x+3(x+5)=30 | | 3-5(4x+5)=78 | | 4(-3+1)=-10(x-4)-14 | | 4x^2-98+180=0 | | 4-7(1-2r)=15.5 | | -29-x=-7x+67 | | 7(x-3)=-3x+89 | | -7+3x-2x=17 | | 5y^5=20 | | 3500+1680x=175000+550x | | 8(3n-8)=8 | | 5.9-p=2 | | x-153=55+9x | | 6.3=7.0x | | -4.5(7x-6.5)=-23.5 | | 52-4x=10-10x | | 3x-2(x-3)+4(x+1)=-5 | | 2x-102-10x=42 | | -9(5-5.5k)=26.5 | | 14-8m= | | -77-10x=165+x | | 5ab*3= | | 5r-14=-44 |

Equations solver categories